Dynamic response-based crack resistance analysis of fibre reinforced concrete specimens under different temperatures and crack depths - Khalel, Hamad Hasan Zedan; Khan, Muhammad; Starr, Andrew (Elsevier, 2023)
Steel fibre-reinforced concrete has been used extensively because of its excellent mechanical properties. Academic researchers have comprehensively discussed the impact and challenges of fibre reinforcement to obtain optimal properties in the resultant concrete. Most researchers reported the mechanical performance of fibre-reinforced concrete (FRC) under static loads. A few studies did conclude the mentioned performance on dynamic loads. However, a comprehensive analysis is still missing that can explain the crack resistance performance of FRC under dynamic loads at relatively high temperatures. In this study, the efficacy of FRC beams for crack resistance is analyzed under coupled loads, i.e., dynamic load at relatively high temperatures as compared to room temperature. Various researchers found that concrete's qualities may change at different temperatures due to moisture content, physical and chemical changes to the ingredients, differences in cooling and heating schedules, water-to-cement ratio, and aggregate. The rate of reduction in moisture content is quite possible even in relatively high temperatures as compared to standard room temperature. Therefore, we selected a range of temperature that demonstrate tests on more realistic weather conditions for most of the concrete applications. As per theory, a slight change in modulus or strength shall definitely effect the dynamic response. Therefore, we tested cantilever FRC beams on a modal excitor in a band heater to expose the beams to bending loads at different temperature values. The variation in the beam's dynamic response parameters, including modal amplitude and frequency, is discussed, and compared with experimental results for regular and reinforced concrete beams. The SIF of plain concrete decreased as concrete temperature increased. Compared to conventional concrete, using SFRC-1 enhanced fracture resistance by 10–20% at various crack depths (2 mm, 4 mm, 6 mm) and temperatures (20 °C, 40 °C, 60 °C).